2022
DOI: 10.25056/jcm.2022.6.2.103
|View full text |Cite
|
Sign up to set email alerts
|

Using nasal septal cartilage-bone complex for anterior septal reconstruction in Asians

Abstract: In Asian rhinoplasty, nasal tip projection and lengthening are often required because of the low nasal tip position and short nose. Anterior septal reconstruction (ASR) is performed for nasal tip projection or lengthening with severe caudal septal deviation. The septal cartilage should be sufficiently large for ASR and other grafting procedures; however, many Asians have a small septal cartilage. Here, we introduce a nasal tip-supporting technique using a septal cartilage-bone complex for Asians with a small s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Notably, these measurements indicated that both nasofrontal and nasolabial angles tended to be more acute than those associated with ideal nose shapes, and the nasal tip was positioned lower than the ideal standard. Consequently, this underscores the importance of dorsal and tip augmentation, along with septal extension, for achieving desirable outcomes in Korean rhinoplasty [9,10]. These findings revealed that the ideal nasofrontal angle for the Korean population differs from previously published values, with a greater inclination [3,5].…”
Section: Discussionmentioning
confidence: 71%
“…Notably, these measurements indicated that both nasofrontal and nasolabial angles tended to be more acute than those associated with ideal nose shapes, and the nasal tip was positioned lower than the ideal standard. Consequently, this underscores the importance of dorsal and tip augmentation, along with septal extension, for achieving desirable outcomes in Korean rhinoplasty [9,10]. These findings revealed that the ideal nasofrontal angle for the Korean population differs from previously published values, with a greater inclination [3,5].…”
Section: Discussionmentioning
confidence: 71%